P029 Pharmacokinetic/Pharmacodynamic Analysis of Amiselimod, a Selective Sphingosine 1-Phosphate Receptor Modulator, in Healthy Subjects: Results From a Phase 1 Study - Lee, Jimin; Lester, Robert; O'Reilly, Terry; Lowe, Ezra; Slatkin, Neal; Franklin, Howard; Israel, Robert (The American journal of gastroenterology, 2021)
Amiselimod is a selective sphingosine 1-phosphate receptor modulator in development for inflammatory bowel disease. It is converted to its active metabolite, amiselimod phosphate (amiselimod-P), and has a long half-life and slow accumulation to steady state. We evaluated a multiple-dose titration regimen to determine the plasma pharmacokinetic (PK) profile of amiselimod and amiselimod-P at steady state for the 0.4 mg QD therapeutic dose on day 13 and for the 0.8 mg QD supratherapeutic dose on day 26. We also investigated the pharmacodynamic (PD) effect of amiselimod on absolute lymphocyte counts (ALCs). A randomized, double-blind, multiple-dose, placebo-controlled, parallel study with a nested crossover design assessed amiselimod and amiselimod-P. Healthy adults received a single dose of placebo followed by oral amiselimod, which was upwardly titrated in doses ranging from 0.4 to 1.6 mg QD to rapidly achieve steady-state concentrations for the 0.4 mg QD and 0.8 mg QD doses within a 28-day treatment period. The PK parameters of amiselimod and amiselimod-P (on days 1, 13 and 26) included the geometric mean (geometric coefficient of variation percentage [CV%]) maximum plasma concentration (Cmax), median (minimum, maximum) time to Cmax (Tmax), geometric mean (geometric CV%) area under the concentration-time curve (AUC) from time 0 to the last measurable concentration, and geometric mean (geometric CV%) AUC from time 0 to 23.5 hours post dose (AUC0-23.5). Multidose PD were evaluated by changes in ALCs. The PK population included 95 amiselimod-treated participants and the PD population included 190 participants who received amiselimod or placebo. On day 13, the steady-state AUC and Cmax for amiselimod 0.4 mg QD increased by 10-fold for amiselimod and by 4-fold for amiselimod-P compared with day 1. On day 26, the steady-state AUC0-23.5 and Cmax for amiselimod 0.8 mg QD increased by 1.9-fold for amiselimod and by 1.8-fold for amiselimod-P compared with day 13. The median Tmax of plasma amiselimod and amiselimod-P were similar on all 3 days and were reached at 11 to 12 hours post dose for amiselimod and at 10 hours post dose for amiselimod-P. The mean ALCs for amiselimod exhibited a gradual decrease from pre-dose (1.681 × 103/uL) to a nadir of 0.424 × 103/uL on day 27. The abbreviated amiselimod dosing titration regimen reached steady state within 14 days for the therapeutic 0.4 mg QD regimen and within 26 days for the supratherapeutic 0.8 mg QD regimen; expected decreases in ALCs were observed following amiselimod.